Georgia Architectural and Historic Properties Survey of Rural [145] Mid western section of the county, Valdosta, Ga. December 1980 - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Rural [145] Mid western section of the county, Valdosta, Ga. December 1980. A one story rectangular plan with hip roof (tin) and asbestos siding. Interior chimney. Sash windows with 4/4 lights. Exposed rafters. Hip dormer. Brick piers. Fair condition. Date of Construction: c. 1905. A typical vernacular house common to these areas of Brooks County.
A one story rectangular plan with hip roof (tin) and asbestos siding. 1 electronic record and assets. Digitized from originals. 1 PDF. 2 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 753 KB (771,683 bytes).
Keywords: Valdosta (Ga.); Historic buildings; Real property surveys; Brooks County (Ga.); Lowndes County Historical Society (Lowndes County, Ga.)